Common Fixed Point Theorems in Complex Valued Metric Space and Application: R. K. Verma, H. K. Pathak - Team, Support (Thai Journal of Mathematics, 2019)
In this paper, we prove some common fixed point results for two pairs of weakly compatible mappings ina complex valued metric space by using a new property. Our result is then applied to prove a common fixed point theorem in GV-fuzzy metric space. These results are the generalization of varioustheorems of ordinary and fuzzy metric spaces.